Application of photovoltaic technology in the use of solar energy - Andjela B Stanojevic (Annals of Environmental Science and Toxicology - Peertechz Publications, 2021)
Solar heating and cooling, concentrating solar power and photovoltaic are three solar technologies which harness solar energy. Photovoltaic Technology (PV) is directly converting sunlight into electricity and it is very convenient to use. In addition, these devices are simple in design and easy to handle. The efficiency of energy production this way is great. In order to obtain constant/continuous energy for consumption, the PV system can be a part of the so-called hybrid system. In the hybrid system, the PV system is combined with other renewable or non-renewable energy sources. However, there are certain problems in the use of solar energy, such as: cost, maintenance of the entire system and the impact of maintenance on the ecosystem, as well as the development of consumer awareness. Today, the world is forced to solve these problems in order to be able to save the planet from further deterioration of the ecosystem.